Liquid metal technology of synthesis of AlOOH anisotropic nanostructured aerogel - R.Sh. Askhadullin; A.A. Osipov; D.A. Skobeev (Nuclear Energy and Technology, 2017)
New method for production of aerogel nanostructures (using the example of AlOOH aerogel) with involvement of liquid metals is examined. In contrast with conventional sol–gel method for producing aerogels the role performed by the alcohol (aqueous) solution is played in the new method by liquid metal in which the base of the future aerogel structure dissociates and assembling of the nanostructure takes place within the gas phase covering the liquid metal. The latter obstacle fundamentally distinguishes the liquid metal method from the conventional technology of aerogel synthesis. Assembling the aerogel structure in the sol–gel method takes place as the result of removal of liquid phase at supercritical parameters which ultimately determines the cost of the products. In the liquid-metal method there is no need to remove the liquid phase, because assembling of fractal nanostructure occurs in the gas phase. Liquid-metal aerogel production method is realized at low (usually atmospheric) pressure without the need to use hazardous and corrosive reagents, and the heat released in the reaction is sufficient for maintaining the desired synthesis temperature. Results of studies of synthesis and properties of ultraporous aluminum oxyhydroxide Al2O3⋅n(H2O) (AlOOH aerogel) produced using the method of selective oxidation of Ga–Al and Bi–Al binary liquid metal fusions by water steam are presented in the present paper. Studies of aerogel properties were performed using methods of scanning electron microscopy (SEM), X-ray diffraction (XRD), synchronous differential scanning calorimetry and thermogravimetry (DSC/TG), as well as by energy dispersive X-ray (EDX) spectroscopy. It was established on the basis of the microstructure analysis performed that the aerogel has space-oriented fibrous nanostructure with “tensile” type anisotropy and fiber diameters varying from 5nm to 15nm. It follows from XRD studies that AlOOH aerogel remains to be amorphous up to 1000°С. Results of studies of thermal physical properties of the aerogel and its elemental composition are presented. It was established that aerogel has low thermal conductivity (∼ 0.01–0.03W/(m⋅K)) within rather wide temperature range from 130 to 1300K.